Epoxidation and di-hydroxylation of camelina sativa oil - Kim, Namhoon (Kansas State University, 2014)
Plant oil-based raw materials have become more attractive alternatives in polymer industry as fossil resources depletion and environmental concerns continue to arise. Camelina (camelina sativa L.) seed contains about 45% of oil and about 90% of the oil is unsaturated fatty acids such as linoleic acid, α-linolenic acid, and erucic acids. It also provides the advantages of low cost and low fertilizer demand. Functionalized oils such as epoxidized camelina oil (ECO) and di-hydroxyl camelina oil (DCO) can be used for resins, adhesives, coatings, etc. The objectives of this work were to synthesize and characterize ECO and DCO from camelina oil. The epoxidation reaction of camelina oil was completed with formic acid and hydrogen peroxide. Catalyst ratio, reaction time, and temperature effects on the epoxidation reaction were studied. The optimum epoxy content of 7.52 wt% with a conversion rate of 76.34% was obtained from camelina oil using excess hydrogen peroxide and a molar ratio of formic acid of less than 1 for 5 hours in 50 °C. Camelina oil yields higher epoxy content (7.52 wt%) than soybean oil (6.53 wt%); however, soybean oil had a higher conversion rate of 80.16% compared to camelina oil because of uniform fatty acids distribution. In this study, we found that epoxidation efficiency is significantly affected by fatty acids composition, structure, and distribution. DCO was synthesized from ECO with different reaction parameters. The ring opening of ECO was performed with water, perchloric acid, and THF as proton donor, catalyst, and solvent respectively. Hydroxyl value of DCO was measured, and the maximal hydroxyl value was 369.24 mg KOH/g. physical properties of DCO were characterized by acid value and moisture content; thermal properties of DCO were obtained using different scanning calorimeter (DSC), thermalgravimetric analysis (TGA). Amount of solvent and acid catalyst addition affected the hydroxyl value and residual acid in DCO. Heat capacity, phase transition temperatures, and thermal stability of DCO were obtained and showed higher values than ECO’s. The DCO showed higher peel adhesion when it was formulated with epoxidized soybean oils through UV curing because camelina oil allows higher epoxy content, which results in higher hydroxyl values.
Keywords: Camelina oil; Epoxidation; Di-hydroxylation; Epoxy content; Biobased products; Chemistry (0485); Polymer Chemistry (0495)